2009
DOI: 10.1144/sp312.7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of organic matter in the fine-grained siliciclastic sediments of the Shemshak Group (Upper Triassic–Middle Jurassic) in the Alborz Range, Northern Iran

Abstract: Bulk organic geochemical and microscopic studies (Rock-Eval pyrolysis, light transmitted-uv microscope) were carried out on the shales of the Upper Triassic-Middle Jurassic Shemshak Group in the northern, central and southern Alborz Range of northern Iran. Total organic carbon (TOC) values range from 0 to 29.4 wt% (1.2 wt% on average) indicating a generally poor-moderate organic carbon content. Upper Triassic shales in the lower part of the Shemshak Group have been mainly deposited in marine/lake settings unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…However, a diorite sill 15 m thick was encountered in the upper part of the Sefid-Sang section (Poursoltani et al, 2007a) and dykes and sills were noted in the outcrop belt by Taheri et al (2009). Although the age of the sill is not known, its presence suggests that the geothermal gradient may have been locally elevated at some period, as was suggested for the Shemshak Group to the west by Shekarifard et al (2009).…”
Section: Thermal Maturationmentioning
confidence: 90%
See 1 more Smart Citation
“…However, a diorite sill 15 m thick was encountered in the upper part of the Sefid-Sang section (Poursoltani et al, 2007a) and dykes and sills were noted in the outcrop belt by Taheri et al (2009). Although the age of the sill is not known, its presence suggests that the geothermal gradient may have been locally elevated at some period, as was suggested for the Shemshak Group to the west by Shekarifard et al (2009).…”
Section: Thermal Maturationmentioning
confidence: 90%
“…1) was the most probable source for the Khangiran Gasfield. Based on RockEval and petrological analysis of 236 shale samples, Shekarifard et al (2009) reported that some Shemshak Group samples contain nearly 30% of total organic carbon, although the average is only 1.2%. Amorphous organic matter derived from marine and non-marine phytoplankton was the predominant organic component, with considerable woody material.…”
Section: Source Rocks For Gasfields In Northeast Iranmentioning
confidence: 99%
“…Its depositional palaeoenvironment includes fluvial, swamp and lake systems, as well as shallow to deeper marine environments with local oxygen-deficient conditions leading to the deposition of organic carbon-rich sediments (Stampfli, 1978;Rad, 1982Rad, , 1986Baudin and Téhérani, 1991;Fürsich et al, 2005;Seyed-Emami et al, 2006;Shekarifard et al, 2009;Fig. 2).…”
Section: Description Of the Shemshak Group And Its Organic-rich Unitsmentioning
confidence: 99%
“…The occurrence of parallel and hummocky structures, marine fauna and trace fossils indicate storm-dominated shelf facies. It is gradually overlain by the Fillzamin Formation (Fürsich et al, 2005; Formation indicate a deepening of the basin (Fürsich et al, 2005Shekarifard et al, 2009). Low mean organic carbon contents are associated to these fully marine and probably oxic sediments of the TAS unit .…”
Section: B Toarcian-aalenian Shales (Tas)mentioning
confidence: 99%
“…The siliciclastic Shemshak Group (Up per Tri as sic-Mid dle Ju rassic) is one of the most ex ten sive lithostratigraphic units of the Iran Plate, wide spread across the north ern Alborz and East Cen tral Iran of the Ira nian plate (Tabas and North of Kerman; Fürsich et al, 2009). Nu mer ous stud ies have doc u mented lithostratigraphic, sedimentological and palaeontological aspects of the Shem shak Group (e.g., Seyed-Emami et al, 2006;Fürsich et al, 2009;Shekarifard et al, 2009;Zanchi et al, 2009;Moosavirad et al, 2011Moosavirad et al, , 2012Abbassi and Madanipour, 2014;Salehi et al, 2017). These stud ies have shown that the Shemshak Group is com posed largely of siliciclastic rock, lo cally reach ing up to 4000 m in thick ness.…”
Section: Introductionmentioning
confidence: 99%